Measurements and modeling of air-broadening coefficients for the ν6 band of CH3I. (May 2020) - Raddaoui, E.; Soulard, P.; Guinet, M.; Aroui, H.; Jacquemart, D.
Highligths: Multispectrum analysis of CH3 I spectra broadened by air. Measurements of air-broadening coefficients. J- and K -rotational model for air-broadening coefficients. Update of a complete CH3 I line list of the ν6 band for atmospheric databases. Abstract: The ν6 band of methyl iodide around 9.5 µ m is studied in terms of air-broadening coefficients. A multi-spectrum fitting procedure is applied to Fourier transform spectra using various mixtures of CH3 I and air in order to retrieve air-broadening coefficients. The numerous measurements performed in this work allow to model the J -and K -rotational dependences of the measured air-broadening coefficients. This model reproduces the measured air-broadening coefficients within standard deviation (1SD) equal to 7%. Comparisons with measurements from literature are performed. Graphical abstract: Image, graphical abstract